The differentiation of osteogenic cells from bone marrow - Bennett, J; Bennett, Jonathan (1991)
According to a current hypothesis there is a putative stromal stem cell in bone marrow, capable of giving rise to adipogenic, osteogenic, fibroblastic and reticular cell lines. An aim of this thesis was to obtain information about the hierarchy and potential for differentiation of these marrow stromal cell lines in young adult rabbits. Particular objectives were to determine the conditions required for expression of the adipocytic phenotype in vitro/ to obtain cloned populations of adipocytic cells and to compare their potential for differentiation with that of populations derived from marrow fibroblastic colonies using an in vivo diffusion chamber (DC) assay. Adipocytic colonies differentiated and grew to a limited size in medium supplemented with rabbit plasma, but attempts to isolate and expand them in this medium failed. On changing the serum supplement to FCS, adipocytic cells acquired a less differentiated morphology. There was a large increase in colony growth and cells were produced in sufficient numbers for the DC assay. 31 fibroblastic and 21 adipocytic colonies were isolated and expanded. Of these, 11 fibroblastic and 8 adipocytic colonies provided enough cells for implantation in DC's. 4 of the 11 fibroblastic and 3 out of the 8 adipocytic colonies formed bone in the chambers. It was concluded that cells which have differentiated in an adipocytic direction are able to revert to a more proliferative stage and subsequently to differentiate along the osteogenic pathway. Adipocytic and fibroblastic cells cultured in vitro from marrow have, with osteogenic cells, a common precursor in adult marrow. Several phenotype specific differentiation markers have been identified for extra-medullary, but not marrow adipocytes. PAL422(AP2), a P2-like myelin protein is a specific marker expressed during differentiation by a number of extramedullary adipocytic cell lines. A further objective was to determine if PAL422(AP2) is expressed in marrow adipocytic cultures, and to asses its value as a marker of adipocytic differentiation in the marrow stromal system. Using western and northern blot analysis, expression of PAL422(AP2) was demonstrated in rat marrow cell cultures then localized to pre-adipocytes and young adipocytes by immunohistochemistry. Thus, PAL422(AP2) is of value as a differentiation marker of marrow adipocytes.